Population Density and Habitat Characteristics of Southern-Cassowary (Casuarius casuarius) at Wasur National Park, Merauke: Kepadatan Populasi dan Karakteristik Habitat Kasuari Gelambir Ganda (Casuarius casuarius) di Taman Nasional Wasur, Merauke - Mawardha, Fahrun Sahara; Perwitasari-Farajallah, Dyah; Mulyani, Yeni Aryati (Jurnal Sumberdaya Hayati, 2025)
Southern Cassowary (Casuarius casuarius) is  a seed disperser of North Australia and Southern Papua lowland forest ecosystem. Despite its dominant distribution in Southern Papua, there is a lack of information regarding its population and habitat characteristics. Due to its high sensitivity, the southern cassowary is rarely seen across the forest, yet the signs of its presence (feces and footprints) are abundant. This study analyzed the distributions, population, and habitat characteristics of the southern cassowary’s in Sota and Wanggo Resort, Wasur National Park, Southern Papua. Maximum Entropy results showed that its distribution focused on the northeastern area of Wanggo Resort and several points north of Sota Resort. Using fecal distance sampling, this study found that the southern cassowary population density in Wasur National Park areas was 0.8 ind/km2, primarily in lowland forests. The area corresponds to the variables that most influence the southern cassowary, which are NDVI, annual precipitation, and distance to the road. These findings underscore the urgency of local stakeholders to pay specific attention to lowland forests in Wasur National Park.